2014
DOI: 10.1176/appi.ajp.2014.13111452
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Expression Patterns of Genes Associated With Neuropsychiatric Disorders

Abstract: Objective Neurodevelopmental disorders presumably involve events that occur during brain development. We hypothesized that neuropsychiatric disorders considered to be developmental in etiology are associated with susceptibility genes that are relatively upregulated during fetal life (i.e. differentially expressed). Method We investigated the presence of prenatal expression enrichment of susceptibility genes systematically, as composite gene sets associated with 6 neuropsychiatric disorders in the microarray-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
81
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 38 publications
9
81
1
2
Order By: Relevance
“…15). We also found that several genes involved in neurodevelopmental disorders 32,33 had increasing A-to-I editing patterns (Supplementary Table 12).…”
Section: Functional Implications Of Increasing A-to-i Editing Patternmentioning
confidence: 70%
“…15). We also found that several genes involved in neurodevelopmental disorders 32,33 had increasing A-to-I editing patterns (Supplementary Table 12).…”
Section: Functional Implications Of Increasing A-to-i Editing Patternmentioning
confidence: 70%
“…Increasing numbers of recent studies have associated specific genes with neurodevelopmental disorders, intellectual disability and autism spectrum disorders (Birnbaum et al 2014;Corvin 2010). These range from genes for different signaling cascades, to apoptosis pathways and synaptic plasticity (Zeidán-Chuliá et al 2014).…”
Section: Potential Biomarkers In Autismmentioning
confidence: 99%
“…Autism related genes are preferentially expressed prenatally in the frontal cortex suggesting that an inherent genetic susceptibility may be confined to this period [6] . Many of these compounds are endocrine disruptors which have been linked to a variety of diseases, including autism, attention hyperactivity deficit disorder, obesity and diabetes, whose incidence has increased in recent decades.…”
Section: Introductionmentioning
confidence: 99%